2016
DOI: 10.1016/j.semcdb.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Auto-fusion and the shaping of neurons and tubes

Abstract: Cells adopt specific shapes that are necessary for specific functions. For example, some neurons extend elaborate arborized dendrites that can contact multiple targets. Epithelial and endothelial cells can form tiny seamless unicellular tubes with an intracellular lumen. Recent advances showed that cells can auto-fuse to acquire those specific shapes. During auto-fusion, a cell merges two parts of its own plasma membrane. In contrast to cell-cell fusion or macropinocytic fission, which result in the merging or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 99 publications
(159 reference statements)
1
12
0
Order By: Relevance
“…1d). This may be related to previously described defects in autofusion in eff-1 mutants [34][35][36] and suggests that miR-1-deficient animals have decreased expression or activity of EFF-1. Notably, trafficking and recycling of EFF-1 are altered upon V-ATPase loss-of-function in the C. elegans hypodermis 37,38 , providing a potential link.…”
supporting
confidence: 69%
“…1d). This may be related to previously described defects in autofusion in eff-1 mutants [34][35][36] and suggests that miR-1-deficient animals have decreased expression or activity of EFF-1. Notably, trafficking and recycling of EFF-1 are altered upon V-ATPase loss-of-function in the C. elegans hypodermis 37,38 , providing a potential link.…”
supporting
confidence: 69%
“…These single-pass transmembrane proteins mediate cell–cell fusion events to form syncytial tissues 20 22 , fuse gametes 26 , and allow viral infection of host cells 25 . EFF-1 and AFF-1 can also mediate cell auto-fusion to shape or repair neuronal dendrites and axons and to generate narrow seamless tubes with intracellular lumens 2 , 15 , 16 , 48 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, other studies in C . elegans revealed that a seamless tube can form by cell wrapping and self-contact to form a seamed tube with an autocellular junction, followed by auto-fusion to eliminate the junction and convert to a seamless toroid 2 , 15 – 17 . Auto-fusion may be a widely used mechanism, since it also generates some seamless tubes in the zebrafish vascular system 18 and in mammalian epithelial cells grown on micropillar arrays 19 ; however, relevant fusogens have not yet been identified in vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…AFF-1, a paralog of EFF-1, is a second C. elegans fusogen displaying a more restricted tissue distribution pattern (Avinoam and Podbilewicz, 2011;Sapir et al, 2007); AFF-1 was not found to be involved in PVD remodeling during development (Oren-Suissa et al, 2017). AFF-1 and EFF-1 fusion proteins also auto-fuse epithelial and myoepithelial cells to form tubes and reshape glial cells (Procko et al, 2011;Rasmussen et al, 2008;Soulavie and Sundaram, 2016;Stone et al, 2009). Moreover, it has recently been demonstrated that in vertebrates auto-fusion takes place in the development of the vascular endothelium, where it leads to pruning of excess blood vessels (Lenard et al, 2015) in a process that remarkably resembles EFF-1-mediated PVD pruning (Oren-Suissa et al, 2010) and that may link EFF-1 to the actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%